Lupus pernio (Besnier-Tenneson syndrome): A rare form of sarcoidosis - Amal Hubail; Roza Belkharoeva; Natalya Tepluk; Tatyana Belerosova (PAGEPress Publications, 2018)
Lupus pernio (LP) is a chronic non-life threatining type of cutaneous sarcoidosis that can be related to chronic fibrotic sarcoidosis, hyperglobulinemia and hypercalcemia. The aim of this case report is to evaluate the clinical and demographic features of cutaneous sarcoidosis mainly presenting with a rare manifestation of LP. In this paper we report a case of systemic sarcoidosis presenting with LP and a review of the available literature. LP is a rare presentation with infiltrated erythematoviolaceous plaques affecting the nose. We address the main management approach, and possible association with an underlying systemic sarcoidosis. LP is a rare but chronic manifestation of systemic sarcoidosis that needs to be treated in order to prevent cosmetic defects and psychological effects. It is important to recognize such a condition early in order to avoid a delay in treatment and worsening of the condition, both physically and psychologically. Further research regarding the diagnostic approach and management is required to understand this condition thoroughly.